2‐(N‐Methylbenzyl)pyridine: A Potential Liquid Organic Hydrogen Carrier with Fast H2 Release and Stable Activity in Consecutive Cycles. Issue 4 (22nd February 2018) - Oh, Jinho; Jeong, Kwanyong; Kim, Tae Wan; Kwon, Hyunguk; Han, Jeong Woo; Park, Ji Hoon; Suh, Young‐Woong
Abstract: Invited for this month's cover is the group of Prof. Young‐Woong Suh at Hanyang University, in collaboration with Dr. Ji Hoon Park at Korea Research Institute of Chemical Technology and Prof. Jeong Woo Han at Pohang at University of Science and Technology. The Cover image is a representation of the H2 economy based on production, storage, and utilization for fuel cell electric vehicles, using our developed liquid organic hydrogen carrier (LOHC) material 2‐( N ‐methylbenzyl)pyridine. The Communication itself is available at 10.1002/cssc.201702256 . Abstract : "The present energy transport infrastructures can be used…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201702256 . View the Front Cover here:10.1002/cssc.201800167 .